Gestão do conhecimento: um estudo no jornalismo regional - Nadai, Fernanda Castro de (2006)
Knowledge is more and more being considered as a main organizational strategic active, mostly in knowledge intensive organizations, as is the case in the Journalism sector; hence slowly we observe an increasing interest for research on knowledge management on this area, particularly regarding ways to improve products and services and helping these kind of organizations to become more competitive. This means creating organizational standards for knowledge processing, as well as developing strategical vision and planning for this purpose. In the Journalism area we observe simultaneously a globalizing trend, pressed by advances on communication technology, as well as a strengthening of local journalism. All this may be considered as part of the Glolocal movement on this Digital Era of Communication, where we deal with real time news at a planetary scale. Under these conditions our research is a case study, based on four interviews on local journals located on the State of São Paulo , looks at the knowledge management processes been used by these kind of organizations related to the four stages of knowledge acquisition, maintenance , stocking and dissemination; as well as problems related to promoting these processes